DAMPAK PENGEMBANGAN KAPAS TRANSGENIK TERHADAP SERAPAN TENAGA KERJA DAN PENDAPATAN DAERAH DI KABUPATEN TAKALAR, BANTAENG, DAN BULUKUMBA - Irsyadi Siradjuddin (Jurnal Agroteknologi, 2012)
This research aim to know : (1) labour Absorption, (2) farmer perception, and (3) Contribution of cotton transgenik to earnings Regency of Takalar, Bantaeng, and Bulukumba. Result of this research indicate that: (1) Development of cotton transgenik in Regency of Takalar, Bantaeng, and Bulukumba have permeated the human capital 3.120 people. (2) Farmer perception of concerning development of cotton transgenik in general good perception. (3) Development of cotton transgenik give the contribution to area earnings. Biggest contribution at Regency of Bulukumba, followed regency of Bantaeng, and Takalar.